Intracapillary Monoclonal IgM Deposition Concomitant With Cold Agglutinin Disease - Silvia M. Titan; Sandra Herrmann; Nelson Leung; Pingchuan Zhang; Stephen Ansell (Kidney Medicine)
Monoclonal gammopathy of renal significance (MGRS) comprises a spectrum of kidney manifestations distinguished by its clinical and pathological presentations. This article reports a case of a female on her 60s who was referred to Nephrology for evaluation of worsening kidney function, hematuria, and proteinuria. Her medical history was notable for marginal zone lymphoma along with immunoglobulin M (IgM)-kappa cold agglutinin disease diagnosed 3 years before the current presentation, which had been treated with rituximab. A kidney biopsy was performed and revealed IgM-kappa monoclonal protein-associated nephropathy with predominantly intracapillary monoclonal IgM deposition injury pattern, a rare form of MGRS, reported for the first time in association with cold agglutinin disease.